Jalabi Practice: a Critical Appraisal of a Socio-Religious Phenomenon in Yorubaland, Nigeria - Musa, Afiz Oladimeji; Ibrahim, Hassan Ahmed (European Center for Science Education and Research, 2015)
Jalabi is an extant historical phenomenon with strong socio-religious impacts in Yorubaland, south-western part of Nigeria. It is among the preparatory Dawah strategies devised by the Yoruba Ulama following the general mainstream Africa to condition the minds of the indigenous people for the acceptance of Islam. This strategy is reflected in certain socio-religious services rendered to the clients, which include, but not limited to, spiritual consultation and healing, such as petitionary Dua (prayer), divination through sand-cutting, rosary selection, charm-making, and an act of officiating at various religious functions. In view of its historicity, the framework of this research paper revolves around three stages identified to have been aligned with the evolution of Jalabi, viz. Dawah, which marked its initial stage, livelihood into which it had evolved over the course of time, and which, in turn, had predisposed it to the third stage, namely syncretism. Triangulation method will be adopted for qualitative data collection, such as interviews, personal observation, and classified manuscript collections, and will be interpretively and critically analyzed to enhance the veracity of the research findings. The orality of the Yoruba culture has greatly influenced the researcher’s decision to seek data beyond the written words in order to give this long-standing phenomenon its due of study and to help understand the many dimensions it has assumed over time, as well as its both positive and adverse effects on the socio-religious live of the Yoruba people of Nigeria.